2019
DOI: 10.3390/su11164397
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Motivation Driven by High Performance Expectations: A Self-Defeating Effect

Abstract: It is generally believed that having high performance expectations is an effective means of motivating employees to pursue excellence and sustain the motivation driven by it, while ignoring the negative impact that hinders the incentive to sustain such expectations. Drawing on the conservation of resources theory, we constructed a moderated mediation model to examine the relationship between supervisor's high performance expectations and the employee's territoriality utilizing data from 291 supervisor-subordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…When leaders show high performance expectations, employees must invest additional resources to reach the required performance outcomes. In line with the job demands-resources model (Bakker & Demerouti, 2007), the use of such supplementary resources to meet high performance expectations could have harmful effects like increasing work stress (Li et al, 2019). This was confirmed by Syrek and Antoni (2014) who found that the relationship between unfinished tasks and negative health outcomes was stronger when leader performance expectations were higher.…”
Section: Expressing Confidence In High Performance and Psmentioning
confidence: 78%
“…When leaders show high performance expectations, employees must invest additional resources to reach the required performance outcomes. In line with the job demands-resources model (Bakker & Demerouti, 2007), the use of such supplementary resources to meet high performance expectations could have harmful effects like increasing work stress (Li et al, 2019). This was confirmed by Syrek and Antoni (2014) who found that the relationship between unfinished tasks and negative health outcomes was stronger when leader performance expectations were higher.…”
Section: Expressing Confidence In High Performance and Psmentioning
confidence: 78%
“…On the other hand, because of the embarrassment of resource constraints, SME outsiders suffer both a reduction in physical resources and an increase in negative cognitive ones, and tend to resist interpersonal knowledge interaction. Leadership performance expectation can also lead to these outsiders' emotional exhaustion and thus to enhancing the sense of resource exhaustion (Li et al, 2019). When SME leaders signal their differential treatment in daily management and resource allocation, individuals who gain sustained high performance expectation perceive more job insecurity.…”
Section: The Moderating Role Of Leadership Performance Expectationmentioning
confidence: 99%
“…This research controlled the impacts of relevant factors, for decreasing possible alternative interpretation for the hypothetical model. We selected and controlled for SME subordinates' basic demographic characteristics, which have been widely as controls in related literatures (Li et al, 2019). Prior literature has suggested that gender, age, job category, highest education and tenure may affect subordinates' knowledge hiding (Abdullah et al, 2019;Banagou et al, 2021;Donate et al, 2022;Jasimuddin and Saci, 2022).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-expectations of medical staff are also higher, but people with high expectations do not always show improvement in performance. Instead, excessive expectations can lead to stress-based reactions such as insomnia and even withdrawal behavior [ 25 ]. Based on the above discussion, we examined the relationship between PSM, work stress, task performance, and turnover intention.…”
Section: Introductionmentioning
confidence: 99%